Straw export in continuous winter wheat and the ability of oil radish catch crops and early sowing of wheat to offset soil C and N losses: A simulation study - Peltre, C.; Nielsen, M.; Christensen, B.T.; Hansen, E.M.; Thomsen, I.K.; Bruun, S. (Agricultural systems, 2016)
The export of winter wheat straw for bioenergy may reduce soil C stocks and affect N losses. Establishing fast-growing catch crops between successive wheat crops could potentially offset some of the C and N losses. Another option is to sow wheat earlier, increasing biomass production during the autumn. The effects of straw export, oil radish catch crop and early sowing of wheat on soil C storage, N leaching losses and N2O emissions were simulated by applying the Daisy model to winter wheat grown continuously for a period of 100years on a sandy loam soil in a Danish climate. The simulations included five levels of initial soil C content (1–3% C), three levels of straw incorporation (0, 50 and 100%), +/− catch crop (oil radish) and two sowing dates (1 and 22 September). Exporting the entire straw production reduced soil C stocks by 1.2 to 14% after 100years, depending on the initial C content. Inclusion of the oil radish catch crop could offset this loss by 2–3 percentage points. Earlier sowing of wheat increased straw production by 18% and reduced loss of soil C by 3–5 percentage points compared to normal sowing time with full straw export. Catch crops and early sowing also reduced N-leaching losses compared to a scenario with full straw export. Early sowing of wheat performed better than the oil radish catch crop in reducing N leaching and N2O emissions. Sensitivity analyses showed that a wetter climate had little effect on soil C storage, but increased N leaching losses by up to 48%. Loss of soil C and leaching of N increased when early-sown wheat was subject to winter-kill and when sandy loam soil was replaced by a sand soil. When wheat is grown continuously, losses of C are mainly defined by the initial soil C content (reflecting the management and land-use history of the soil) and by the level of straw export. The use of oil radish catch crops and early sowing of wheat may offset some of the adverse effects of straw export. •Exporting all harvestable straw reduced soil C stocks.•The soil C loss was highly affected by the initial C content.•Some of the soil C loss was offset by using oil radish catch crop and early sown wheat.•Oil radish catch crops and early sown wheat reduced N leaching losses.•Early sowing reduced N leaching and N2O emission more than oil radish catch crop.